Respuesta :

Answer:

[tex]x = 5[/tex]

Step-by-step explanation:

25 - 3x = -5(1 - x) - 2x

We have to first get rid of the parenthesis:

[tex]-5 * 1[/tex]  ==>  -5

[tex]-5 * -x[/tex]  ==>  5x

So now you should have:

25 - 3x = -5 + 5x - 2x

Combine like terms:

25 - 3x = -5 + 5x - 2x

25 - 3x = -5 + 3x

Add 3x to both sides:

25 - 3x  =  -5 + 3x

    + 3x  =      + 3x

And you should have:

25 = -5 + 6x

Add 5 to both sides:

25 = -5 + 6x

+5 = +5

30 = 6x

Divide 6 to both sides:

[tex]\frac{30}{6}[/tex]     =      [tex]\frac{6x}{6}[/tex]

5 = x

Answer:

5

Step-by-step explanation:

First you would multiply -5 by everything in parenthesis so...

25 - 3x= -5 + 5x - 2x

Then 5x- 2x..

25 - 3x= -5 + 3x

Add -3x to both sides

25 = -5 + 6x

Add 5 to both side

30= 6x

Divide 6 on both side

5 = x

Hope this helped :)